Consumption of fibre rich foods : comparative study in different countries - Guiné, Raquel Pinho Ferreira (Array, 2020)
Foods such as fruit, vegetables, and cereals, and particularly whole grain, are rich in dietary fibre and have been proved to have multiple beneficial effects for the human health. The present research was designed to assess some eating practices related to fibre-rich foods in different countries, namely Argentina, Croatia, Hungary, Latvia, Portugal, and Romania. A cross-sectional descriptive study was undertaken on a sample of 4905 adult participants, obeying all ethical guidelines for this type of research. Regarding the data treatment, basic statistics was complemented with the tree classification analysis. Generally, the results show a low consumption of salads and vegetables, i.e., up to 11 servings/week (for 78.2% of participants), with Croatia in the lead (86.6%). Regarding fruit, a great majority of data also indicated low consumption (92.3%), most especially for Latvia (98.3%). The level of consumption of whole cereals was also low (72.6%), particularly for Latvia (90.0%). The tree classification analysis showed that while the first discriminant variable for the consumption of salads and vegetables was country, followed by education, for the consumption of fruit, it was country and then sex, and finally, for the consumption of whole cereals, it was sex and followed by country. The results allowed the conclusion that the consumption of foods rich in dietary fibre was very low for these countries, highlighting the necessity to implement strategies that incentivise the consumption of such foods, which are very important for a healthy diet.